Brief Report: Acute Kidney Injury in People Living With HIV Hospitalized With Coronavirus Disease 2019. (15th August 2021) - Fisher, Molly C.; Fazzari, Melissa J.; Hanna, David B.; Patel, Viraj V.; Felsen, Uriel R.; Alahiri, Emad; Byju, Arjun; Akiyama, Matthew J.; Ginsberg, Mindy S.; Anastos, Kathryn; Ross, Michael J.
Abstract : Background: Data on clinical characteristics and outcomes of people living with HIV (PLWH) hospitalized with coronavirus disease 2019 (COVID-19) who develop acute kidney injury (AKI) are limited. Setting: Large tertiary health care system in the Bronx, NY. Methods: We performed a retrospective cohort study of 83 PLWH and 4151 patients without HIV hospitalized with COVID-19 from March 10, 2020, to May 11, 2020. We compared the clinical characteristics and outcomes associated with AKI by HIV serostatus and evaluated HIV-related factors for AKI among PLWH. AKI was defined and staged using Kidney Disease Improving Global Outcomes criteria. Results: The incidence of AKI in hospitalized patients with COVID-19 did not differ significantly by HIV serostatus (54.2% in PLWH vs 49.5% in patients without HIV, P = 0.6). Despite a higher incidence of stage 3 AKI (28.9% vs 17.1% P = 0.05) in PLWH compared with those without HIV, there was no significant difference in the need for renal replacement therapy (22.2% vs 13.4% P = 0.12), renal recovery (76.9% vs 82.5% P = 0.61), or dependence on renal replacement therapy (7.7% vs 3.8% P = 0.27). CD4 T-cell count, HIV-1 RNA viral suppression, and antiretroviral therapy use were not associated with AKI. AKI was associated with increased need for invasive ventilation and in-hospital death, but HIV was not an independent risk factor of in-hospital death after AKI [adjusted hazard ratio 1.01 (95% CI: 0.59 to 1.72), P = 0.98]. Conclusions: HIV-related factors were not associated with increased risk of AKI in PLWH hospitalized with COVID-19. PLWH hospitalized with COVID-19 had more stage 3 AKI, but outcomes after AKI were similar to those without HIV. Abstract : Supplemental Digital Content is Available in the Text.